Knowledge and Attitudes of Pregnant Women Towards Dietary Supplements and Alternative Medicine for the City of Mosul - Eman Luay, Salwah H. Almukhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Alternative medicine is a term used to describe treatments that may receive along with traditional medicine. Examples of aalternative medicine include massage, meditation, biofeedback, tai chi, reiki, music therapy, guided imagery, herbal medicines and dietary supplements. This study aimed to Determine pregnant women's knowledge and attitudes about dietary supplementation and alternative medicine. Methodology and materials: A Cross-Sectional study design was used to achieve the present study's objectives from the 10th of December 2021 to the 1st of March 2022. A structured interviewing questionnaire was used to collect data from 250 pregnant women at Al Khansa, Al Salam, Al-Batool, and Mosul General hospitals in Mosul city. Results: The majority (62.8%) of pregnant women's age group was (21-30), and the mean age was of mothers (28.4). (51.6%) of the pregnant were homemakers, (31.2%) were employees, and knowledge of pregnant women using supplements was 1.7973, while knowledge of pregnant women using alternative medicine was 1.627. Pregnant women's attitudes about nutritional supplements and alternative medicine are 2.9331 Conclusion: the knowledge level about supplements and alternative medicine was moderate, and this knowledge was associated with their attitudes. There is a significant relationship between demographic information and their knowledge and attitudes, while BMI and husband occupation were insignificant. Recommendation: Ministry of Health must adopt education through health promotion programs about the safe use of dietary supplements and alternative medicine for pregnant women and better understand the reasons and facilitators. Also, encourage pregnant women through different media to consulate the doctors and nurses before using any nutritional supplement or alternative medicine to prevent complications and side effects. Keywords: Knowledge, pregnant, Mosul, Iraq.